English for Academic Purposes: Theory, Trends and Practices - Pandey, Gopal Prasad (Education and Development, 2019)
English for academic purpose (EAP) emerged as a branch of English for specific purposes in the early 1980s. EAP grounds English language teaching in the linguistic demands of academic context, tailoring instruction to specific rather than general purposes. There is a growth of interest in EAP in the recent years. The interest in EAP developed in response to the growing need for intercultural awareness and of English as a lingua franca (ELF). EAP has become a major area of research in applied linguistics and focus of the courses studied worldwide by a large number of students preparing for study in colleges and universities. The increase in students’ undertaking tertiary studies in English-speaking countries has led to a steady demand for the courses tailored to meet the immediate, specific vocational and professional needs. Thus, most universities in the present day world prioritize the role of academic skills. The aim of the paper is to examine the key approaches to the teaching of English for academic purposes, current trends in teaching EAP, and to argue the centrality and significance of EAP in the academia. The paper concludes by arguing that a greater emphasis needs to be placed on methodology in EAP.